2021
DOI: 10.3390/en14051404
|View full text |Cite
|
Sign up to set email alerts
|

Visual Characteristics of Afterimage under Dark Surround Conditions

Abstract: Three psycho-visual experiments were carried out to investigate visual afterimage characteristics of high luminance LEDs under dark surround conditions. The results show that the luminance of illumination, exposure time and background luminance are the primary factors influencing the afterimage’s duration, the color difference between stimulus and background, and visibility. Besides, visual afterimage characteristics are strongly correlated with the luminance contrast between the stimulus and the background, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…If we talk about the rate of disappearance of the afterimage, then different values are known here: from hundreds of milliseconds [7,1315] to tens of seconds or more [5,16, 17]. The relaxation time of the afterimage is known to be 4-8 seconds [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If we talk about the rate of disappearance of the afterimage, then different values are known here: from hundreds of milliseconds [7,1315] to tens of seconds or more [5,16, 17]. The relaxation time of the afterimage is known to be 4-8 seconds [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the brightness of the object, exposure time and background brightness were the main factors affecting the duration of the afterimage, the color difference between the stimulus and the background, and visibility [5]. At the same time, for black-and–white images, if the object was brighter than the background, then the afterimage was positive, if the background was lighter, then the afterimage was negative [5,6]. At the same time, it was found that bright afterimages caused by a decrease in brightness were stronger and lasted longer than dark afterimages created by brightness increments of equal sizes [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation